James Joyce: The Daedalus Connections - Stewart, Bruce (ABEI Journal, 2012)
In 1904 James Joyce began using the pseudonym “Stephen Daedalus” both as a nom de plume and a signature in letters to his friends. In the autobiographical novel Stephen Hero, the name is given to the protagonist while in A Portrait of the Artist as a Young Man (1916) it is simply contracted to “Dedalus” – the “strange name” that which Stephen recognises as his own and the “queer name” which his college friends attribute to him. Stephen Dedalus lives on in Ulysses and has a mirror-life as Shem the Penman in Finnegans Wake. We think we know that Joyce discovered his pseudonym in the eighth tale in Ovid’s Metamorphoses from which he took the epigraph for A Portrait. It may not be so. This article explores the Dedalus connections in various works such as Giordano Bruno’s writings and Samuel Taylor Coleridge’s writings on Bruno.